Effectiveness of Sleep Deprivation in Treating Acute Bipolar Depression as Augmentation Strategy: A Systematic Review and Meta-Analysis - Ramirez-Mahaluf, Juan P.; Rozas-Serri, Enzo; Ivanovic-Zuvic, Fernando; Risco, Luis; Vöhringer, Paul A. (Frontiers in Psychiatry, 2020)
Background: Bipolar disorder is a disabling disease characterized by the recurrence of mood episodes. Successful strategies for the acute treatment of bipolar depression are still a matter of controversy. Total sleep deprivation (TSD) has shown acute antidepressant effect; however, the prompt relapse of depressive symptoms after sleep recovery has been reported. Taking this into consideration, we aimed to address a two-fold research question: what are the acute effects of adding TSD to pharmacological treatment and what are the acute and chronic effects of adding medications to TSD. Methods: MEDLINE, Embase, Cochrane Central Register of Controlled Trials and ClinicalTrials.gov databases were searched for clinical trials assessing bipolar depression and TSD. Two independent reviewers selected and classified 90 abstracts. The outcomes we assessed were change in Hamilton Depression Rating Scale (HDRS) or Montgomery-Asberg Depression Rating Scale (MADRS), sustained long-term response rate, treatment-emergent mania or hypomania, and tolerability (using dropout rates as a proxy). The compared groups were: TSD alone versus TSD plus medications, and medications alone versus medications plus TSD. Data was analyzed using Stata 16.0. Results: Patients treated with TSD plus medications compared with medications alone showed a significant decrease in depressive symptomatology after one week (SMD -0.584 [95% CI -1.126 to -0.042], p=0.03. Also, a significant decrease in depressive symptomatology (SMD -0.894 [95% CI -1.388 to -0.399], p<0.001) was found in the group with TSD plus medications compared with TSD alone, at the 10th day of treatment. We meta-analyzed the long-term effect of the TSD. It showed a sustained antidepressant effect (log OR = 2.365 (95% CI 0.95 to 3.779, p<0.001) in the group where TSD was combined with medication when compared with patients treated only with TSD. Finally, no differences in tolerability (log OR = 0.234 (95% CI -1.164 to 1.632, p=0.74) or affective switch were found. Conclusion: Adding TSD to medications to bipolar depression treatment resulted in an augmentation in acute response. We also found that medications have a positive impact in acute response when added to TSD. Furthermore, this higher response rate was maintained after 3 months while keeping Lithium therapy.